2000
DOI: 10.1111/j.1365-2141.2000.02408.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the angiotensin‐converting enzyme gene deletion polymorphism on the risk of venous thromboembolism

Abstract: Summary. Allele frequencies for the insertion/deletion (I/D) polymorphism of the angiotensin-converting enzyme (ACE) gene were determined in a large case±control study of 517 unselected patients with venous thromboembolism and 478 blood donors. The D allele frequency was 0´53 [95% confidence interval (CI) 0´50±0´56] in patients and 0´54 (95% CI 0´50±0´57) in controls, giving an odds ratio for the D allele of 0´97 (95% CI 0´81±1´16). In the same population, the odds ratio for the factor V Leiden mutation (F5G16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 6 publications
(4 reference statements)
1
34
0
Order By: Relevance
“…14 Moreover, it has been assumed that the I allele has a sequence similar to a silencer sequence, which might explain why the D allele is associated with higher ACE levels than the I allele. 15 ACE activity and ACE I/D polymorphism were not found to be associated with PE in previous studies, 9,16,17 but no information is available about the effect of this polymorphism on maternal-fetal hemodynamics in women at high risk of PE.…”
mentioning
confidence: 84%
“…14 Moreover, it has been assumed that the I allele has a sequence similar to a silencer sequence, which might explain why the D allele is associated with higher ACE levels than the I allele. 15 ACE activity and ACE I/D polymorphism were not found to be associated with PE in previous studies, 9,16,17 but no information is available about the effect of this polymorphism on maternal-fetal hemodynamics in women at high risk of PE.…”
mentioning
confidence: 84%
“…Thus, it was thought that the ACE I/D gene polymorphism was not a risk factor in patients with thromboembolism. 26 In another study, Isbir et al determined a relationship between arteriovenous graft (AVG) thrombosis and ACE I/D genotype. They found higher risks in the ID genotype when compared with II and DD genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Prandoni's study (2007) of patients with venous thrombosis showed a moderate increase in risk for male patients with the DD genotype, but no increase in risk for women patients with the same genotype. Jackson et al (2000) in another case-control study of 500 unselected patients showed that the ID polymorphism in the ACE gene was not a risk factor for venous thromboembolism. Lopaciuk et al (2010) analyzed the genetic profiles of 38 patients who had a postoperative symptomatic pulmonary embolism or proximal deep venous thrombosis after arthroplasty, and 241 control subjects without thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Two of its most common polymorphisms are -401 G/T and -402 G/A. These polymorphisms of the promoter region of the FVII gene are associated with changes in FVII blood levels, and represent important risk factors for quantitative cardiovascular diseases, including ischemic heart disease and arterial or venous thrombosis (Jackson et al, 2000;Eroğlu et al, 2010Eroğlu et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation